Adaptively secure attribute-based encryption for traitor tracing - ying MAHai; sun ZENGGuo; ping CHENJian; hua WANGJin; jun WANGZhan (Tongxin xuebao)
For the key abuse problem in attribute-based encryption (ABE),each user was identified by his unique identity, and the collusion secure codes and the traitor tracing mechanism were introduced to the ABE scheme. The definition,security model and tracing model for adaptively secure attribute-based encryption for traitor tracing (ABTT)were forma-lized,and an adaptively secure ABTT scheme was proposed,which may trace traitors in policy-specific pirate decorders. Under these subgroup decision assumptions in composite groups and the DDH assumption,adaptively secure and can adaptively trace traitors were proved. Therefore, the scheme not only was capable of tracing adaptively traitors in policy-specific pirate decorders,but also further strengthens the security of ABE system,which has theoretical and prac-tical values.